How toxic is the depleted uranium to crayfish Procambarus clarkii compared with cadmium?. Issue 2 (12th September 2014) - Al Kaddissi, Simone; Simon, Olivier; Elia, Antonia Concetta; Gonzalez, Patrice; Floriani, Magali; Cavalie, Isabelle; Camilleri, Virginie; Frelon, Sandrine; Legeay, Alexia
ABSTRACT: Due to a lack of information on the assessment of uranium's (U) toxicity, our work aimed to compare the effects of U on the crayfish Procambarus clarkii with those of the well documented metal: cadmium (Cd). Accumulation and impacts at different levels of biological organization were assessed after acute (40 µM Cd or U; 4–10 days) and chronic (0.1 µM Cd or U; 30–60 days) exposures. The survival rates demonstrated the high tolerance of this species toward both metals and showed that Cd had a greater effect on the sustainability of crayfish. The concentration levels of Cd and U accumulated in gills and hepatopancreas were compared between both conditions. Distinctions in the adsorption capacities and the mobility of the contaminants were suspected. Differences in the detoxification mechanisms of both metals using transmission electron microscopy equiped with an energy dispersive X‐ray were also pointed out. In contrast, comparison between the histological structures of contaminated hepatopancreas showed similar symptoms. Principal component analyses revealed different impacts of each metal on the oxidative balance and mitochondria using enzymatic activities and gene expression levels as endpoints. The observation that U seemed to generate more oxidative stress than Cd in our conditions of exposure is discussed. © 2014 Wiley Periodicals, Inc. Environ Toxicol 31: 211–223, 2016.